USING PORPE METHOD TO IMPROVE READING COMPREHENSION OF SECOND YEAR STUDENTS AT SMP N 21 PEKANBARU - Elidar '; Mahdum '; Erni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Based on the writer’s preliminary study, it was found that, the students could not apply their reading to other reading texts, they only knew about readings in their text book at the school. This problem was caused by some factors. For example, some students could not understand about content of reading text and identify the detailed information of the text. So, the writer was interested in carrying out the research about this problem. The research was administered at SMP N 21 Pekanbaru. The subject of the research is the second year students at SMP N 21 Pekanbaru, and the object of this research is the using Predict, Organize, Rehearse, Practice and Evaluate method to improve reading comprehension. This research is Pre-Experimental design and the type of the research is the Static-Group Comparison.The population of this research was all of the second year students. The total number of population was 371 students. Because the number of population was large, the researcher used cluster sampling by taking two classes only as sample; VIII.3 consisted of 38 students as experimental group, and VIII.5 consisted of 38 students as control group, so the numbers of sample from two classes were 76 students. To analyze the data, the researcher adopted paired sample t-test formula by using SPSS. After analyzing the data, the researcher found that there is significant effect of using PORPE method to improve reading comprehension the second year students of SMP N 21 Pekanbaru, where T-table is at the 5% grade of significance that refers to 2.02. While in the level of significance 1% is 2.72. Therefore, it can be analysis that to is higher than t table in either at 5% or 1% grade of significance. It can be read that 2.02<11.483>2.72.Keywords: Predict, Organize, Rehearse, Practice and Evaluate, Method, Reading Comprehension